Temporary Investment Tax Incentives: Theory with Evidence from Bonus Depreciation - House, Christopher L; Shapiro, Matthew D (American Economic Review, 2008)
The intertemporal elasticity of investment for long-lived capital goods is nearly infinite. Consequently, investment prices should fully reflect temporary tax subsidies, regardless of the investment supply elasticity. Since prices move one-for-one with the subsidy, elasticities can be inferred from quantities alone. This paper uses a recent tax policy—bonus depreciation—to estimate the investment supply elasticity. Investment in qualified capital increased sharply. The estimated elasticity is high—between 6 and 14. There is no evidence that market prices reacted to the subsidy, suggesting that adjustment costs are internal, or that measurement error masks the price changes. (JEL G31, H32)